Redefining Disability to Promote Equality: The Role of Disability Studies in Educating Occupational Therapists - Wright, Beth Ann (Disability Studies Quarterly, 2004)
Disability Studies (DS) can retain its integrity and potentially expand its role in progressive occupational therapy (OT) programs. The leaders of the OT profession are endorsing a broader view of disability as a universal human condition consistent with the World Health Organization's (WHO's) International Classification of Functioning, Disability and Health (ICF) instrument. This article examines the role Disability Studies might play in the education of OT's. First, preeminent scholars in the field of OT endorse the development of the WHO's ICF instrument. Second, allied Health Professions, such as OT, who embrace the use of the ICF instrument help preserve, rather than destroy the fundamental framework of disability studies as well as the medical model. Third, both OT and DS can examine external environmental factors, such as the law, as relevant contextual factors to improve the health status of individuals with disabilities under the WHO's ICF instrument.